Cardiometabolic disease and features of depression and bipolar disorder: Population-based, cross-sectional study. (April 2016) - Martin, Daniel J.; Ul-Haq, Zia; Nicholl, Barbara I.; Cullen, Breda; Evans, Jonathan; Gill, Jason M. R.; Roberts, Beverly; Gallacher, John; Mackay, Daniel; McIntosh, Andrew; Hotopf, Matthew; Craddock, Nick; et al.
Abstract : Background: The relative contribution of demographic, lifestyle and medication factors to the association between affective disorders and cardiometabolic diseases is poorly understood. Aims: To assess the relationship between cardiometabolic disease and features of depresion and bipolar disorder within a large population sample. Method: Cross-sectional study of 145 991 UK Biobank participants: multivariate analyses of associations between features of depression or bipolar disorder and five cardiometabolic outcomes, adjusting for confounding factors. Results: There were significant associations between mood disorder features and 'any cardiovascular disease' (depression odds ratio (OR) = 1.15, 95% CI 1.12–1.19; bipolar OR = 1.28, 95% CI 1.14–1.43) and with hypertension (depression OR = 1.15, 95% CI 1.13–1.18; bipolar OR = 1.26, 95% CI 1.12–1.42). Individuals with features of mood disorder taking psychotropic medication were significantly more likely than controls not on psychotropics to report myocardial infarction (depression OR = 1.47, 95% CI 1.24–1.73; bipolar OR = 2.23, 95% CI 1.53–3.57) and stroke (depression OR = 2.46, 95% CI 2.10–2.80; bipolar OR = 2.31, 95% CI 1.39–3.85). Conclusions: Associations between features of depression or bipolar disorder and cardiovascular disease outcomes were statistically independent of demographic, lifestyle and medication confounders. Psychotropic medication may also be a risk factor for cardiometabolic disease in individuals without a clear history of mood disorder.